Dubbing Translation Technique in the Animated Film of Frozen: Party is Over - Purwani Indri Astuti; Nunun Tri Widarwati; Ratih Wijayava; Muamaroh Muamaroh (Script Journal: Journal of Linguistics and English Teaching, 2022)
Background: Dubbing is an interesting translation for movie viewers because viewers do not need to be constrained by reading the subtitling on the monitor. However, with all its limitations dubbing is a challenge for a translator. Frozen: Party is over is an intriguing film to investigate. Methodology: All utterances of the characters in the film are becoming the research data. The numbers of data were 62 for words, phrases and sentences and analyzed using Molina & Albir's translation theory. The interactive model of Miles and Huberman analyzed all the data. Findings: The result of the research is that the translation techniques used by the translator were modulation, established equivalent and literal. The most dominant technique used by the translator was literal. This is because children consume the film, so most of the sentences are simple sentences. Conclusion: The translation techniques used by the translator were modulation, established equivalent and literal. Originality: This research focused on the dubbing translation technique for the animated film Frozen: Party is over. In comparison, other research with the same object discussed topics such as deixis, language styles, illocutionary act and subtitling.